A mathematical formulation for the cell-cycle model in somitogenesis: analysis, parameter constraints and numerical solutions. - McInerney, D; Schnell, S; Baker, R; Maini, P (2004)
In this work we present an analysis, supported by numerical simulations, of the formulation of the cell-cycle model for somitogenesis proposed in Collier et al. (J. Theor Biol. 207 (2000), 305-316). The analysis indicates that by introducing appropriate parameter constraints on model parameters the cell-cycle mechanism can indeed give rise to the periodic pattern of somites observed in normal embryos. The analysis also provides a greater understanding of the signalling process controlling somite formation and allows us to understand which parameters influence somite length.